2012
DOI: 10.1259/bjr/36231529
|View full text |Cite
|
Sign up to set email alerts
|

Patient experiences of MR colonography and colonoscopy: a qualitative study

Abstract: Objectives: The aim of this study was to apply qualitative techniques to assimilate data on patient experience and attitudes during MR colonography (MRC) and colonoscopy (CC). Methods: 18 patients (11 male, 8 female, median age 40.5 years), 10 of whom had known colonic inflammatory bowel disease (IBD) and 8 who were under investigation for suspected colonic neoplasia (non-IBD), underwent MRC and conventional CC. Semistructured interviews were performed to assimilate test experiences and preferences, and themes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 10 publications
2
21
0
Order By: Relevance
“…These first mentioned advantages and disadvantages were opposite in OC. It is evident that such elements can be disadvantages and advantages in colonoscopy performed without general anesthesia, as reported by both symptomatic patients [6,21,22] and screening individuals [5,23,24], and are recently reported from both qualitative studies, cohort studies and register research [21][22][23][24][25][26][27][28]. They thereby support our findings of a possible distribution of advantages and disadvantages in OC.…”
Section: Discussionsupporting
confidence: 89%
“…These first mentioned advantages and disadvantages were opposite in OC. It is evident that such elements can be disadvantages and advantages in colonoscopy performed without general anesthesia, as reported by both symptomatic patients [6,21,22] and screening individuals [5,23,24], and are recently reported from both qualitative studies, cohort studies and register research [21][22][23][24][25][26][27][28]. They thereby support our findings of a possible distribution of advantages and disadvantages in OC.…”
Section: Discussionsupporting
confidence: 89%
“…There was male predominance in our study which supported by the study of Papporadio et al and Hartmann et al we have observed that family history has present in 42.85% patient and gastrointestinal bleeding was the most common indication for evaluation of patients. 10,11 This finding corroborates with the study of Hafeez et al 13 Hartmann et al has reported that GI bleeding in 65.7% which is higher than our study. 11 In present study most commonly legion was found in ascending colon followed by sigmoid codon, caecum and rectum this finding corroborate with the observation of Neals et al but is not supported by the work of Laiw et al 14,15 Regarding number of patients with polyp, all for all size of polyp true positive cases were 48 and true negatives cases were 52.…”
Section: Discussionsupporting
confidence: 93%
“…After the initial screening 53 abstracts were selected for full text review and eight studies were determined to be eligible. A manual review of references yielded a further two eligible studies ( 25 , 26 ) ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%